Cobalt Catalyzed Reductive Spirocyclopropanation Reactions. Issue 2 (22nd November 2019) - Werth, Jacob; Berger, Kristen; Uyeda, Christopher
Abstract: Cobalt pyridine−diimine (PDI) complexes catalyze the reductive spirocyclopropanation of terminal 1, 3‐dienes. gem ‐Dichlorocycloalkanes serve as carbene precursors and Zn is used as a terminal electron source. The reaction is effective for a range of gem ‐dichloro partners including those containing sulfur and nitrogen heterocycles. An example of an intramolecular Rh‐catalyzed [5+2]‐cycloaddition of a vinyl spirocyclopropane is demonstrated, providing rapid access to a complex tricyclic framework. Overall, this catalyst system is capable of suppressing the kinetically facile 1, 2‐hydride shift, which has hampered the development of Simmons−Smith reactions using Zn carbenoids possessing β‐hydrogen atoms. Abstract :